2018
DOI: 10.1093/omcr/omx106
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, low-dose of clarithromycin as a cause of community-acquired Clostridium difficile infection in a 5-year-old boy

Abstract: Clostridium difficile is one of the most common causes of antibiotic-associated diarrhoea. Despite C. difficile infection (CDI) has increased in all ages worldwide, episodes of CDI are often misdiagnosed due to the lack of clinical suspicion. Macrolides are also associated with CDI. Additionally, exposure to macrolides in the 12 weeks preceding infection is reported to be a significant risk factor of CDI in a child. We report here a 5-year-old Japanese boy who presented with acute onset of watery diarrhoea. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Risk factors may include increasing outpatient antibiotic prescriptions, acid-suppression medications, asymptomatic carriers in the community, and food or water contamination [135]. A sub-group analysis of a population-based epidemiological study of CDI in Olmsted County, Minnesota in 1991–2005 [136], identified 157 CA-CDI cases (75% women), with a median age of 50 years.…”
Section: Risk Factors For Community-acquired C Difficile Infectionmentioning
confidence: 99%
“…Risk factors may include increasing outpatient antibiotic prescriptions, acid-suppression medications, asymptomatic carriers in the community, and food or water contamination [135]. A sub-group analysis of a population-based epidemiological study of CDI in Olmsted County, Minnesota in 1991–2005 [136], identified 157 CA-CDI cases (75% women), with a median age of 50 years.…”
Section: Risk Factors For Community-acquired C Difficile Infectionmentioning
confidence: 99%
“…Clindamycin, cephalosporins, and fluoroquinolones are considered as major antibiotics associated with CDI [ 6 ]. Food or water contamination, gastric acid-suppression, and asymptomatic carriage in the community are the potential risk factors of community acquired CDI [ 7 ]. One-third of the total CDI burden occurring in the USA in 2011 was community-associated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%